2017
DOI: 10.1002/iid3.159
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of interleukin‐37 in cardiovascular diseases

Abstract: IntroductionInterleukin (IL)‐37 is a newly identified member of the IL‐1 family, and shows a growing role in a variety of diseases. This review aims at summarizing and discussing the role of IL‐37 in cardiovascular diseases.MethodsData for this review were identified by searches of MEDLINE, Embase, and PubMed using appropriate search terms.ResultsIL‐37 is a newly identified cytokine belonging to the IL‐1 family and is expressed in inflammatory immune cells and several parenchymal cells. It has potent anti‐infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 60 publications
(83 reference statements)
0
20
0
1
Order By: Relevance
“…Our results show an enhanced expression of caspase-1 in mice with EAE that were treated with H-hPDLSCs-CM. IL-37, once translocated into the nucleus, prevents the transcription of proinflammatory cytokines and chemokines, such as IL-1α, IL-6, TNF, and CXCL2 (45, 47, 48). In agreement with this, we observed decreased levels of the proinflammatory cytokines, INF-γ and IL-17, after H-hPDLSCs-CM administration (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show an enhanced expression of caspase-1 in mice with EAE that were treated with H-hPDLSCs-CM. IL-37, once translocated into the nucleus, prevents the transcription of proinflammatory cytokines and chemokines, such as IL-1α, IL-6, TNF, and CXCL2 (45, 47, 48). In agreement with this, we observed decreased levels of the proinflammatory cytokines, INF-γ and IL-17, after H-hPDLSCs-CM administration (37).…”
Section: Discussionmentioning
confidence: 99%
“…The level of IL-37 is normally low, but this signi cantly increases under severe in ammatory conditions. It has been previously found that IL-37 plays an important regulatory role in the development of several in ammatory and autoimmune diseases [37,38]. Recent studies investigated that IL-37 mediates a variety of anti-cancer effects in multiple types of cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 37 (IL-37) is also known as IL-1 family member 7 (IL-1F7). The cytokine exists in its five splice variants (a-d), which were discovered and given different names in the past [337] , [338] . Of these splice variants, isoform b (or IL-37b) is the most prevalent and widely studied.…”
Section: Miscellaneous Inhibitors Of Tlr Signaling That Are Not Direcmentioning
confidence: 99%
“…Although mice do not produce IL-37, human IL-37 functions as a potent anti-inflammatory cytokine. On one hand SIGIRR KO mice are hyper-responsive to LPS and other TLR agonists, on the other hand, IL-37 transgenic mice are relatively resistant to TLR agonists [337] , [338] . Inhibition of IL-37 activity by siRNA significantly increase the production of several pro-inflammatory mediators (IL-1β, IL-1α, GM-CSF, C-CSF, IL-6, and TNF-α) from human PBMCs when stimulated with either LPS or Pam3CSK4 [341] .…”
Section: Miscellaneous Inhibitors Of Tlr Signaling That Are Not Direcmentioning
confidence: 99%